Influence of pH, O2, and temperature on the absorption properties of the secondary light-harvesting antenna in members of the family Rhodospirillaceae. - Uffen, R L (1985)
In some Rhodospirillaceae, the primary light-harvesting (LH I) antenna absorbs near-infrared light around 870 nm, whereas LH II (holochrome B800-860) has a major absorption band between 850 and 860 nm (B860) and a minor absorbancy around 800 nm (B800). Results show that, unlike LH I, holochrome B800-860 (LH II) exhibits unstable light absorption properties in whole cells. This was observed in Rhodopseudomonas capsulata grown anaerobically in light in weakly buffered carbohydrate medium; cultures lost both carotenoid-dependent brown-yellow pigmentation and LH II absorbancy. The whole cell spectrophotometric changes were attributed to mild acid conditions generated during sugar metabolism. LH II absorbancy was also destroyed in both R. capsulata and Rhodopseudomonas gelatinosa when cultures growing at neutral pH were acidified to a pH value around 5.0 with HCl. In contrast, during the same time period of exposure to pH 5.0, only a 50% decrease in Rhodopseudomonas sphaeroides LH II B800 absorbancy was measured. At neutral pH, LH II absorbancy in suspensions of nongrowing Rhodopseudomonas spp. was also sensitive to O2 exposure and to incubation at 30 to 40 degrees C. During treatment with O2, the rate of LH II B800 absorption decrease in R. gelatinosa and R. sphaeroides was 60 and 40% per h, respectively, compared with their absorbancy maximum around 860 nm. Both 860-nm absorbancy and the total bacteriochlorophyll content of the cells remained unchanged. On the other hand, no significant decrease in B800 if LH II in R. capsulata occurred during O2 exposure, but a 20% absorption decay rate per h of B800 was observed in cells incubated anaerobically at 40 degrees C. These B800 LH II spectral changes Rhodopseudomonas spp. were prevented by maintaining cells at neutral pH and at 10 degrees C. The near-infrared absorption spectrum of Rhodospirillum rubrum, which does not form LH II, was not significantly influenced by these different pH, aerobic, or temperature conditions.